Penguasaan Bahasa Inggris Masyarakat dan Partisipasinya dalam Pengembangan Desa Wisata - Rahadi, Irwan; Nursaly, Baiq Rismarini; Handini, Baiq Suprapti; Murcahyanto, Hary (JOEAI (Journal of Education and Instruction), 2021)
This study aims to determine the level of community English mastery and community participation in the development of tourist villages both in decision making, implementation, benefits and evaluation. This research use desciptive qualitative approach. data collection using in-depth interviews (in-dept-interview), observation and documentation. while the technical data analysis is using the Miles and Huberman technique with data processing stages such as data collection, data reduction, data presentation, and data verification. Based on the data and the results of the analysis, information was obtained and it was concluded that the community's mastery of English is still weak, especially in terms of finding information, explaining the location profile, local cultural customs and helping to communicate with the general public, the use of English is still limited to greetings, explaining about objects. travel and exchange of information. The form of community participation is still very less than optimal, only in taking visible benefits, while other aspects such as in decision making, implementation and community evaluation have never been involved. The community is only given a place to open a business/trade shop, transport goods or porters, guides, rent climbing equipment, open parking lots at the tourism location. Keywords: English, community participation, tourism.